1998
DOI: 10.1002/(sici)1099-1379(199803)19:2<131::aid-job878>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of procedural justice context

Abstract: SummaryUsing a multilevel framework, we hypothesized that both employee perceptions of procedural justice and a work unit level measure of procedural justice context would be associated with employee reports of job satisfaction and organizational commitment. Three hundred and twenty-three employees from 53 branches of a ®nancial services organization were used to test this hypothesis. Hierarchical linear modeling analyses revealed that procedural justice context explained variance in employee job satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
201
1
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(209 citation statements)
references
References 28 publications
5
201
1
2
Order By: Relevance
“…Masterson et al, (2000) in their study find that procedural justice is an effective predictor of employees' degree of satisfaction; decisions which have been taken in a fair way tend to please employees more than when decisions are perceived to be taken in an unjust way resulting into dissatisfaction (Cropanzano & Greenberg, 1997). Mossholder et al, (1998) conclude that dynamics of job satisfaction can be well explained by the procedural justice. Other studies suggest that if the processes and procedures of organization are perceived to be fair by employees, they tend to get more satisfied, more willing to accept the resolution of the procedures, and more likely to nurture a higher organizational commitment (Bingham, 1997;Tyler and Lind, 1992).…”
Section: Procedural Justice As a Determinant Of Job Satisfactionmentioning
confidence: 99%
“…Masterson et al, (2000) in their study find that procedural justice is an effective predictor of employees' degree of satisfaction; decisions which have been taken in a fair way tend to please employees more than when decisions are perceived to be taken in an unjust way resulting into dissatisfaction (Cropanzano & Greenberg, 1997). Mossholder et al, (1998) conclude that dynamics of job satisfaction can be well explained by the procedural justice. Other studies suggest that if the processes and procedures of organization are perceived to be fair by employees, they tend to get more satisfied, more willing to accept the resolution of the procedures, and more likely to nurture a higher organizational commitment (Bingham, 1997;Tyler and Lind, 1992).…”
Section: Procedural Justice As a Determinant Of Job Satisfactionmentioning
confidence: 99%
“…These have reported that employees within the same group share common perceptions of justice in the organisation, as indicated by a significant variation in justice perceptions both within and between work groups. [51][52][53] Implications In addition to effects on mental health, failure to ensure fair treatment may lead to low morale, reduced work output and quality of service, and lost resources-because people who are trained and experienced leave the organisation. 54 While the increased risk of psychiatric morbidity associated with an adverse change in relational justice gives cause for concern, the fact that a favourable change decreases the risk gives cause for optimism.…”
Section: Study Limitationsmentioning
confidence: 99%
“…This measure originally had six items. However, only five items out of original six items were used by Birnbaum and Somers (1993), McFarlin and Rice (1992), Mossholder, Bennett, and Martin (1998), and Williams, Gavin, and Williams (1996). The coefficient alphas of those five items were reported in range of .81 to .89 (as cited in Fields, 2002).…”
Section: R Upretymentioning
confidence: 99%